Optical Behavior of PANI/Sno2 Nanocomposites - Owusu-Sekyere, Kofi; Nkrumah, Isaac; Nkum, R. K.; Singh, K. (European Scientific Journal, ESJ, 2017)
This article reports the synthesis of Polyaniline (PANI) in Emeraldine form by in situ chemical oxidation method by using Ammonium persulphate as an oxidizing agent and a simultaneous synthesis of polyaniline (PANI)/SnO2 nanocomposites. The UV-Vis absorption spectra were studied to explore the optical behavior after incorporating SnO2 nanoparticles into PANI matrix. The absorption bands for the PANI/SnO2 sample were observed at 370nm, 550 nm and 910 nm wavelengths. This, however shows significant shifts in the absorption spectral to higher wavelength when comparing the absorption spectrum of both PANI and PANI/SnO2. These bands may well correspond to ?-?* transition, polaron-?* transition and polaron-? transition, respectively. This could be attributed to the successful interaction of the SnO2 with the polymer chain. Hence, such shifts in absorption peak positions are related to the presence of the SnO2 in the matrix of PANI. The Attenuated Total Reflectance (ATR) spectrum of PANI/SnO2 provided the characteristic absorption peaks at 3227.54cm-1,1569.03cm-1, 1496.71cm-1, 1444.86cm-1, 1289.13cm-1, 1145.65cm-1,821.57cm-1, 506.68cm-1, and 412.08cm-1 due to the provision of information about the changes in the chemical structure of polymer. ATR spectra also give indication that the incorporation of SnO2 in the matrix of PANI seems to be effective for the improvement of the physicochemical properties of conducting polymers.